Applying Uncertain Science to Nature-Based Coastal Protection: Lessons From Shallow Wetland-Dominated Shores - Möller, Iris (Frontiers in Environmental Science, 2019)
Climate change and associated sea-level rise alongside the potential for alterations in the magnitude and frequency of extreme storm events, rapidly rising coastal populations, and a legacy of coastal land reclamation are forcing the need for sustainable coastal protection on shallow, wetland-dominated coasts. In this context, practitioners, and academics in the field of coastal flood and erosion risk reduction have been highlighting the flood protection value of natural coastal features for some time. Examples of the implementation of nature-based coastal flood and erosion risk reduction schemes, however, are few and far between and can certainly not (yet) be considered mainstream. One key problem around the implementation of these types of approaches has arguably been the relative lack of perceived scientific certainty around the efficiency with which natural landforms, such as coastal wetlands, reduce wave action on landward lying structures and the persistence of such landforms in an uncertain future. This makes nature-inclusive approaches less attractive to more traditional engineering-only approaches that rely solely on one “hard” structure with a well-defined impact on waves and a specified design life. Using the example of wave dissipation over coastal wetland surfaces, this paper provides a way forward for an easily applicable scientifically informed assessment of the minimum difference any given wetland makes to wave heights at landward locations. Such a “minimum function” approach could be rolled out to other ecosystem services provided by natural features and thus allow decision makers and coastal planners to consider nature-inclusive approaches to coastal management with greater confidence.